Roy Lichtenstein: all about art. - Berman, Avis, ....- (Louisiana : Louisiana Museum Modern Art, 2003)
A catalogue to accompany a major exhibition of Lichtenstein's work in London, this volume includes essays by Avis Berman and others as well as transcripts of David Sylvester's 1997 interview with the artist and a chronology of the artist's life.
Keywords: Grafische kunst